Case Report of Ipilimumab-Induced Diffuse, Nonnecrotizing Granulomatous Lymphadenitis and Granulomatous Vasculitis. (April 2018) - Arellano, Kari; Mosley, James C.; Moore, Donald C.
Ipilimumab is indicated for the treatment of melanoma in both the metastatic and adjuvant setting. Ipilimumab inhibits cytotoxic T-lymphocyte antigen 4, leading to the augmentation of T-cell activity and an antitumor immune system response. The side effect profile of ipilimumab consists of autoimmune-like events such as dermatitis, colitis, and thyroiditis. These immune-related adverse events can be serious, often resulting in the need for systemic immunosuppression with corticosteroids. We present a case of diffuse, nonnecrotizing granulomatous lymphadenitis and granulomatous vasculitis in a heavily pretreated patient with metastatic melanoma. After completion of 4 cycles of ipilimumab for the treatment of metastatic melanoma, our patient complained of increasing fatigue, drenching night sweats, and chills. Imaging revealed diffuse adenopathy involving several lymph nodes. Biopsy was positive for nonnecrotizing granulomatous lymphadenitis and granulomatous vasculitis. High-dose prednisone was initiated and tapered gradually over 6 weeks, resulting in complete resolution of the granulomatous disease.